Patient safety incidents identified by the caregivers of hospitalized children - Letícia Maria Hoffmann; Wiliam Wegner; Cecilia Biasibetti; Merianny de Ávila Peres; Luiza Maria Gerhardt; Márcia Koja Breigeiron
ABSTRACT Objective: to analyze patient safety incidents identified by caregivers of hospitalized children. Method: a qualitative, exploratory-descriptive study was carried out with 40 caregivers of children hospitalized in three hospital institutions in the city of Porto Alegre, Rio Grande do Sul State, Brazil, from April to December 2016. Semi-structured, recorded and transcribed interviews were carried out in their entirety, submitted to a thematic analysis using the NVivo 11.0 software. Results: reports related to falls, infant feeding, patient/caregiver identification, medication process, communication, hand hygiene and hygiene of the hospital environment, spread of diseases, relations between caregivers and professionals and care processes/procedures were all cited. Final considerations: communication and the relations among caregivers and professionals are the main contributory factors for patient safety incidents, interfering with the quality of care. The participation of caregivers and engagement in child care may be strategies to be developed to promote a safety culture.